The Road to Price Stability - Orphanides, Athanasios (American Economic Review, 2006)
Nearly a quarter-century after Paul Volcker’s declaration of war on inflation on October 6, 1979, Alan Greenspan declared that the goal had been achieved. Drawing on the extensive historical record, I examine the views of Chairmen Volcker and Greenspan on some aspects of the evolving monetary policy debate and explore some of the distinguishing characteristics of the disinflation.